2021
DOI: 10.1371/journal.pntd.0009152
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal clustering of Mountain-type Zoonotic Visceral Leishmaniasis in China between 2015 and 2019

Abstract: With several decades of concerted control efforts, visceral leishmaniasis(VL) eradication had almost been achieved in China. However, VL cases continue to be detected in parts of western China recent years. Using data of reported cases, this study aimed to investigate the epidemiology and spatio⁃temporal distribution, of mountain-type zoonotic visceral leishmaniasis (MT-ZVL) in China between the years 2015 and 2019. Epidemiological data pertaining to patients with visceral leishmaniasis (VL) were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
2
10
0
Order By: Relevance
“…The disease caused by Leishmania has been frequently reported in Shanxi province, which recorded 21.7% of the total mountain-type zoonotic visceral leishmaniasis cases between 2015 and–2019 in China, and, therefore, it is viewed as one of the hotspot regions for visceral leishmaniasis [ 42 ]. Furthermore, previous studies based on real-time quantitative PCR suggested that the average prevalence of Leishmania was 1.98% in female Ph.…”
Section: Discussionmentioning
confidence: 99%
“…The disease caused by Leishmania has been frequently reported in Shanxi province, which recorded 21.7% of the total mountain-type zoonotic visceral leishmaniasis cases between 2015 and–2019 in China, and, therefore, it is viewed as one of the hotspot regions for visceral leishmaniasis [ 42 ]. Furthermore, previous studies based on real-time quantitative PCR suggested that the average prevalence of Leishmania was 1.98% in female Ph.…”
Section: Discussionmentioning
confidence: 99%
“…As a momentous parasitic disease, VL has been brought under control in China ( Wang et al, 2000 ). However, with the development of society and the improvement in the ecological environment, the incidence of MT-ZVL rocketed rapidly and generated new hotspots in central China recently ( Zhou et al, 2020a , b ; Guan et al, 2021 ; Hao et al, 2021 ). Therefore, the objective of this study was to retrospectively analyze the epidemiology and spatiotemporal distribution characteristics of VL in China from 2019 to 2021, aiming to provide insights into the prevention and control of VL.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial increase in the incidence of MT-ZVL in China may be related to the emergence of VL in the historically endemic areas and the formation of some new hotspot areas of MT-ZVL ( Zhou et al, 2020c ; Guan et al, 2021 ; Hao et al, 2021 ). Between 2019 and 2021, a total of 27 new reemerged historically endemic counties were identified that were mainly located in Shanxi, Shaanxi, Henan, and Hebei Provinces and Beijing municipality, where 54 VL cases were notified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the topography was also considered an important indicator of MT-ZVL transmission risk. Historically, MT-ZVL was closely related to topography and was mainly distributed in hilly settings of Gansu, Sichuan, Shanxi, Shaanxi, western Henan, and northern Hebei, Qinghai, Ningxia, Liaoning, and the suburbs of Beijing [34]. These areas were mainly extension areas of the Loess Plateau, which provides a suitable habitat for wild reservoirs hosts and sand ies to maintain the MT-ZVL transmission cycle [14,35].…”
Section: The Degree Of Coordination Of Expert Opinionsmentioning
confidence: 99%